Noninvasive ventilation for acute respiratory failure in children – a systematic review - Gonzaga,Carolina Silva (2011)
ABSTRACT Objective: To assess the role of noninvasive ventilation in the treatment of children with acute respiratory failure. Methods: A systematic review of literature on noninvasive ventilation in MEDLINE, LILACS, EMBASE, and Cochrane databases, besides references in articles. The outcomes evaluated were responses in blood oxygenation and ventilation, and patient survival. Results: A total of 120 studies on noninvasive ventilation were found as of May, 2010. Of these, only 19 were about noninvasive ventilation in children. On the other hand, there are prospective and cohort clinical trials leading to a level II quality of evidence concerning the use of noninvasive ventilation in children. Conclusion: There is scientific evidence for proposing the use of noninvasive ventilation, with a B-II degree of recommendation.